Response surface optimisation and antioxidant characterisation of high antioxidant soft jelly prepared from Baccaurea angulata fruit juice and Trigona sp. honey using central composite design - Mat Alewi, Nur Aizura; Ibrahim, Muhammad; Md Isa, Muhammad Lokman; Abdull Rasad, Mohammad Syaiful Bahari; Abdul Rafa, A. A.; Anuar, Mohd Nur Nasyriq (Universiti Putra Malaysia, 2020)
The optimum combination of Baccaurea angulata fruit juice (X1 : 15 - 85 ratio) and Trigona sp. honey (TH) (X2 : 15 - 85 ratio) in developing a high antioxidant soft jelly was investigated based on the antioxidant capacity (Y1 ), phenolic (Y2 ), and flavonoid (Y3 ) content. Response surface methodology (RSM), via central composite design (CCD), was used to produce optimal combination effects of the two independent variables (B. angulata fruit juice and TH) for highest recovery of antioxidant capacity (AC), total phenolic content (TPC), and total flavonoid content (TFC). The polynomial models generated were satisfactory. The lack-of-fit test were higher than p > 0.05 for all three analyses, signifying the suitability of the models in accurately predicting the variations. Predicted values of the analysis agreed with those of the experimental values. An optimum combination of B. angulata fruit juice and TH was developed (ratio 40:40). The sample also exhibited significant FRAP and DPPH radical scavenging activities. Several polyphenols were identified for the samples through UHPLC-MS/MS. In conclusion, B. angulata and Trigona sp. honey have high potentials to be used in fortifying the soft jelly samples, making them prospective food supplements due to their nutritional and health benefits